Islamic Fundamentalism in Late-Colonial Indonesia: The Persatuan Islam Revisited - Howard M. Federspiel (Al-Jami'ah: Journal of Islamic Studies, 1999)
Persaman lslam, secara urnum dikenal sebagai organisasi yang cukup berpengaruh dalam tulisan keislaman di Indonesia pada awal abad kedua puluh. Meskipun tidak banyak menaruh perhatian dalam bidang politik, namun ide-idenya yang modern dan fundamentalistis serta ideologinya yang mumi mampu dianggap sebagai warisan yang penting dalam membentuk identitas lslam di Asia Tenggara. Organisasi yang didirikan oleh sekelompok cendekiawan muslim di Bandung pada tahun 1923 ini mempunyai sistem pengajaran yang berbeda dari sisrem yang banyak berlaku pada saat itu. Jika para ulama tradisionalis (kyai) menerapkan sistem pengajaran dengan pendekatan guru-murid, maka Persis menggunakan sistem klasikal. Berkaitan dengan materi yang diajarkan,75% adalah pelajaran agama dan 25% untuk pelajaran umum, khususnya dikelas-kelas dasar, adapun untuk kelas-kelas diatasnya perbandingannya adalah 50:50. Sebagai organisasi lslarn Persis mempunyai prinsip "memajukan Islarn dengan berdasar pada al-Qur'an dan al-Hadis." Para tokohnya menganggap diri mereka sebagai ulama baru yang berusaha membersihkan agama dari segala bid'ah, serta mengdaptasikan prinsip-prinsip agama pada kondisi kontemporer. Untuk menyebarkan ajaran-ajarannya digunakan majalah disamping sarana-sarana yang lain. Ada empat majalah yang diterbitkan antara uhun 1929 - 1941 yaitu ; Pambela Islam, al-Lisan, at-Fatwa dan. At-Taqwa. Gerakan yang telah dilakukan Persis ini dapat disejajarkan dengan apa yang telah dilakukan oleh para pembaharu yang lain semisal al-Afgani, Abduh dan Rasyid Rida. [The Persatuan Islam (Islamic Union; Persis) is generally recognized as an influential organization " in Indonesian Islamic writing on the twentieth century for its attempts to apply Islamic teachings to the Indonesian religious environment.2 While considered generally out of touch with political reality, its modernist, fundamentalist and ideological message has been regarded as an important legacy in the building of an Islamic identity in Southeast Asia. While the movement has moved to a very minor role in contemporary Indonesian Muslim activity, in its heyday in the 1930's and 1950's, it was an influential actor in both the Islamic community of Indonesia and on the political stage of those eras. The academic study of this movement was undertaken first by a Dutch administrator-scholar in the 1950’s in official reports and in a published study in the 1960's,3 and later through a dissertation and two ancillary studies by an American scholar in the l960's and 1970's.4 Since the appearance of those studies several Indonesian scholars have written studies of the movement and one Indonesian scholar has contributed a new dissertation on the legal teachings of one of its prominent activists.5  In view of these new studies and an extensive review of the original source materials of the movement, this essay reexamines the earlier evaluations and compares them with other Islamic thinkers movements of the twentieth century to gain fuller perspective of the persatuan Islam and its place in indonesia history. The focal point of this assessment is on the movement in the last two decades of Dutch rule in the lndies from approximately 1923 to 1942, which is the initial period of Persatuan lslam activity. What emerges from this reassessment is a fuller understanding of the role of the movement and its place in the Islamic activities of its day.]